"Sons of the Empire" Dance and the New Zealand Male - Schultz, Marianne 1966- (Edinburgh: Edinburgh University Press, 2011)
RESUMEN: This article traces the journeys of dancing man from the stages of New Zealand to the stages of London during the twentieth century. The oft-repeated history of "the hard man" of New Zealand who belonged to the "culture of imperial manliness" is challenged by the stories of these men who beginning in the 1920s with Jan Caryll, became professional dancers. I argue that within early twentieth-century New Zealand culture the opportunity existed for men and male bodies tone on display. The Maori haka, which featured man dancing in public exhibitions and ceremonies, had been seen by non-Maori (Pakeha) since first contact, while the emergence of body-building, beginning with the visit in 1902 of Eugen Sandow and a culture of sport, allowed men to be on show. Not least of all, tours to the antipodes of European dancers inspired young man to study ballet and contemporary dance. As a consequence, throughout the twentieth century. New Zealand male dancers continued to arrive in London and contributed to both New Zealand and British dance histories.